EXTRACTION OF STRONTIUM(II)BY CROWN ETHER: INSIGHTS FROM DENSITY FUNCTIONAL CALCULATION - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The structures, energetic and thermodynamic parameters of crown ethers with different cavity size, electron donating/withdrawing substituent groups and donor atoms have been determined with density functional method at B3L YP level of theory in gas and solvent phase. Small core quasi-relativistic effective core potentials was used together with the accompanying SDD basis set for S²and DZPbasis set was used for crownether atoms. Natural bond orbital (NBO) analysis was evaluated to characterize the distribution of electrons on the complexes. The interaction energy is well correlated with the values of Strontium charge after complexation, the second order interaction energies (Ell and HOMO-LUMO energy gab (AEgab). The interaction energy and thermodynamics parameters in gas phase are reduced in solvent phase as the solvent molecules weaken the metal-crown ether interaction. The thermodynamic parameters indicated that less feasibility to extract S²+ ion directly from pure water without presence of organic solvent. The theoretical values of extraction energy for Sr(N03)2 salt from aqueoussolution in different organic solvent is validated by the experimentaltrend. This study would have strong contributionin planning the experimentsto the design of specific host ligand and screening of solvent for extraction of metal ion.